Magmatic Evolution during the Cretaceous Transition from Subduction to Continental Break-up of the Eastern Gondwana Margin (New Zealand) documented by in-situ Zircon O–Hf Isotopes and Bulk-rock Sr–Nd Isotopes. (16th May 2018) - van der Meer, Q H A; Waight, T E; Tulloch, A J; Whitehouse, M J; Andersen, T
ABSTRACT: Major changes in tectonic style can lead to tapping of highly variable magma sources and potentially result in significant episodes of crustal growth. Here we focus on magmatism associated with a transition from arc magmatism to subsequent over-thickening and eventual orogenic collapse. This transition is associated with cessation of subduction and was followed by continental extension and finally continental break-up as recorded in the Cretaceous magmatic record of Zealandia. Orogenic collapse peaked at ∼110 Ma and is expressed through core complex formation and the intrusion of I- to evolved I/S-type Rahu Suite plutons that have widely varying chemical compositions but homogeneous whole-rock and zircon isotopic signatures that are intermediate between mantle and local upper crust values. The Rahu Suite is interpreted to be derived from differing degrees of melt extraction from a pre-existing lower crustal source and lacks a demonstrable juvenile component. This lower crustal source was likely formed by magmatic underplating and melt–crust hybridization during preceding arc volcanism (Separation Point and Darran suites), effectively smearing out a pulsed event of crust formation in the zircon record. Therefore, late orogenic I- and I/S-type suites do not have to equate to crustal growth and can be an expression of crustal re-melting. An abrupt change in magma sources in Zealandia occurred after 100 Ma during the onset of progressive crustal extension. A juvenile alkaline component (presumably derived from the lithospheric mantle) is suggested to have been present from >97 Ma. This component became more pronounced with time until the emplacement of granites and trachytes with isotopic signatures overlapping with coeval mafic mantle-derived dikes during bimodal rift-related magmatism. The juvenile alkaline component dictated the composition of the felsic magmas but did not represent a significant crustal growth event due to small total volumes.